2014
DOI: 10.1530/erc-14-0106
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of gastrointestinal neuroendocrine tumours: implications for treatment

Abstract: In the past few years, there have been advances in the treatment of neuroendocrine tumours (NETs) and improvements in our understanding of NET biology. However, the benefits to patients have been relatively modest and much remains yet to be done. The 'Hallmarks of Cancer', as defined by Hanahan and Weinberg, provide a conceptual framework for understanding the aberrations that underlie tumourigenesis and to help identify potential targets for therapy. In this study, our objective is to review the major molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 145 publications
(154 reference statements)
1
35
0
2
Order By: Relevance
“…The complexity of cancer has been reduced to a defined number of underlying principles (Hanahan & Weinberg 2000) which have been recently updated (Hanahan & Weinberg 2011). This approach has been transposed to NET disease (Walenkamp et al 2014). Using networking analysis, cancer hallmarks can be signified by molecular networks which have the advantage of allowing quantification and computational modeling .…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of cancer has been reduced to a defined number of underlying principles (Hanahan & Weinberg 2000) which have been recently updated (Hanahan & Weinberg 2011). This approach has been transposed to NET disease (Walenkamp et al 2014). Using networking analysis, cancer hallmarks can be signified by molecular networks which have the advantage of allowing quantification and computational modeling .…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature remains lacking in therapeutically useful knowledge [1,12,13,14,15]. As part of this study, we compared NLR and PLR with respect to the parameters with prognostic importance for NETs, and the subsequent survival analysis presented significant NLR and PLR findings for NETs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent sequencing studies have indicated that pathways regulating chromatin remodelling and epigenetic modifications are frequently altered in NETs [18,19]. As a result, targeting of deregulated epigenetic mechanisms has emerged as a possible novel treatment strategy in NETs [20,21]. Valproic acid (VPA), an inhibitor of class I and class IIa HDACs, has recently been tested in phase II studies on patients with metastatic NETs with promising results [22].…”
Section: Introductionmentioning
confidence: 99%